Peningkatan Hasil Belajar Siswa Melalui Penggunaan Media Pembelajaran Berbasis Website Di Sekolah Dasar - Huriyyatul Kamila, Nur; Prasetyo, Teguh; Retnadi Rias Hayu, Wiworo (Buletin Ilmiah Pendidikan, 2023)
This study aims to determine the use of Web-based learning media in improving student learning outcomes in class IV at SDN No. 178491 Pohan Door, Toba Samosir Regency. Pre-research results show that teachers rarely use media or materials that can motivate students. This contradicts the 2013 Curriculum, which emphasizes using electronic media to prevent boredom during learning. The research was conducted for three months, from November 2022 to January 2023, with 16 fourth-grade students as research subjects. This study uses classroom action research carried out in two cycles. Qualitative data were analyzed using qualitative descriptive analysis by comparing cycles I and II. In contrast, quantitative data on student learning outcomes were analyzed using descriptive comparative analysis by comparing initial test scores, cycles I and II. The results showed that using Web-based learning media significantly increased the learning outcomes of fourth -grade students at SDN No. 178491 Pohan Door, Toba Samosir Regency. The average student learning outcomes increased from 62.50 at the beginning of the study to 73.13 at the end of cycle I and increased again to 85.63 at the end of cycle II. The initial completeness level of 12.50% increased to 50% at the end of cycle I and again to 100% at the end of cycle II. The results of the observer's assessment showed that student activity and teacher performance also increased from cycle I to cycle II. In conclusion, the application of Web-based learning media can positively impact student learning outcomes, increasing the level of completeness, student activity, and teacher performance. Therefore, it is suggested that teachers use Web-based learning media in the learning process to motivate and improve student learning outcomes.